Catalysis with Chalcogen Bonds. (16th December 2016) - Benz, Sebastian; López‐Andarias, Javier; Mareda, Jiri; Sakai, Naomi; Matile, Stefan
Abstract: Herein, we introduce catalysts that operate with chalcogen bonds. Compared to conventional hydrogen bonds, chalcogen bonds are similar in strength but more directional and hydrophobic, thus ideal for precision catalysis in apolar solvents. For the transfer hydrogenation of quinolines and imines, rate enhancements well beyond a factor of 1000 are obtained with chalcogen bonds. Better activities with deeper σ holes and wider bite angles, chloride inhibition and correlation with computed anion binding energies are consistent with operational chalcogen bonds. Comparable to classics, such as 2, 2′‐bipyrroles or 2, 2′‐bipyridines, dithieno[3, 2‐b;2′, 3′‐d]thiophenes (DTTs), particularly their diimides, but also wide‐angle cyclopentadithiazole‐4‐ones are identified as privileged motifs to stabilize transition states in the focal point of the σ holes on their two co‐facial endocyclic sulfur atoms. Abstract : Im Brennpunkt : Die Einbeziehung von Chalkogenbindungen in nichtkovalente katalytische Systeme wurde realisiert, einhergehend mit tiefen σ‐Löchern und weiten Bisswinkeln zwischen den kofacialen endocyclischen Schwefelatomen von Dithieno[3, 2‐b;2′, 3′‐d]thiophenen (DTTs). Die Systeme aktivieren Hydridakzeptoren für die Transferhydrierung von Chinolinen und Iminen durch molekulare Erkennung freier Elektronenpaare im Übergangszustand.